The Influence of Leadership Style, Work Motivation and Work Discipline on Employee Performance at PT Mega Buana Karya Sukses - Azahra, Salsabila Aulia; Widigdo, Aslam Mei Nur (Universitas Mercu Buana, 2025)
The primary goal of this study is to determine how different types of leadership, employee motivation, and workplace discipline affect productivity at PT Mega Buana Karya Sukses. A total of 38 employees participated as respondents in this survey. A saturation sampling strategy was employed in this investigation. Quantitative methods based on a causal model were used in the investigation. This study employed SPSS 26 to conduct its statistical analysis, which included multiple linear regression. Employee performance was positively affected by leadership style, job motivation, and work discipline, according to the research.